1998
DOI: 10.1111/j.1539-6924.1998.tb01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and the Perception of Risks and Accidents

Abstract: Identifying the causes of accidents is a necessary prerequisite for preventive action. Some research suggests however that the analysis of accidents does not only differ between experts and laymen but that it is also linked to certain characteristics inherent in the analyst and in the social group to which he belongs: beliefs, value systems, norms, experiences in common, attitudes, roles, social and technical practices, etc. Culturally determined bias seems to affect the perception of risk and the causes of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
79
1
19

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 28 publications
13
79
1
19
Order By: Relevance
“…More specifically, the more FLMs perceived that operators under their supervision were exposed to frequent and serious risks the more they got involved in safety management. This first finding corroborates several studies showing that perceived risk positively related to behavior ( Arezes and Miguel, 2008;Brewer et al, 2007;Gandit et al, 2009;Gyekye, 2006;Kouabenan, 1998Kouabenan, , 2009Kuttschreuter, 2006;Weinstein et al, 2007). It shows that first-line managers' awareness of their supervisees' exposure to risk is a triggering element for their greater concern about safety issues.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…More specifically, the more FLMs perceived that operators under their supervision were exposed to frequent and serious risks the more they got involved in safety management. This first finding corroborates several studies showing that perceived risk positively related to behavior ( Arezes and Miguel, 2008;Brewer et al, 2007;Gandit et al, 2009;Gyekye, 2006;Kouabenan, 1998Kouabenan, , 2009Kuttschreuter, 2006;Weinstein et al, 2007). It shows that first-line managers' awareness of their supervisees' exposure to risk is a triggering element for their greater concern about safety issues.…”
Section: Resultssupporting
confidence: 88%
“…Studying the perception of risks by people exposed to them seems to be gaining traction as a way to promote greater involvement in safety-related actions and increase their effectiveness as well (Arezes and Miguel, 2008;Gandit et al, 2009;Gyekye, 2006;Ji et al, 2011;Kuttschreuter, 2006;Kouabenan, 1998Kouabenan, , 2009Kouabenan et al, 2007;Rundmo, 2001;Weinstein et al, 2007;Mbaye and Kouabenan, 2013). Numerous observations and studies attest the link between risk perception and protective behavior.…”
Section: Perceived Risk and Safetymentioning
confidence: 99%
“…The results of this research showed that fatalistic beliefs significantly predicted occupational SA among workers. This is consistent with the findings of previous studies (34)(35)(36)(37) and can be interpreted on the basis of the following possibilities. First, According to the cultural theory of risk (34), cultural settings and values, such as fatalistic beliefs have an important role in shaping risk perception and SA in individuals.…”
Section: Discussionsupporting
confidence: 93%
“…The only marked differences between men and women concerned the risks associated with domestic activities and public transportation (see also Barke et al 1997;, and the only differences between artists and scientists concerned health risks. Among the other personal dimensions considered one can cite income (e .g., Flynn et al 1994;Palmer 2003), religious orientation (e .g., af Wahlberg 2002), political preferences (e .g., Sjöberg 2000), risk attitude (e .g., Vollrath et al 1999;Sjöberg 2003), values (e .g., Sjöberg 2000), social trust (e .g., Vicklund 2003Siegrist et al 2000), anxiety (e .g., Bouyer et al 2001;Källmén 2000), self-efficacy (e .g., Kouabenan 1998;Källmén 2000), locus of control (e .g., Källmén 2000), worldviews (e .g., Bouyer et al 2001;Brenot et al 1998), and classical personality factors (e .g., Sjöberg 2003). Typically, the part of the variance in risk assessment explained by all these personal factors has proven to be low (Sjöberg 2003).…”
Section: Societal Risk Perceptionmentioning
confidence: 99%